Students' Information Literacy: A Perspective from Mathematical Literacy - Wijaya, Ariyadi (Journal on Mathematics Education, 2016)
Information literacy is mostly seen from the perspective of library science or information and communication technology. Taking another point of view, this study was aimed to explore students' information literacy from the perspective of mathematical literacy. For this purpose, a test addressing Programme for International Student Assessment (PISA) mathematics tasks were administered to 381 eighth and ninth graders from nine junior high schools in the Province of Yogyakarta. PISA mathematics tasks which were used in this test had specific characteristics regarding information processing, i.e. containing superfluous information, having missing information, and requiring connection across information sources. An error analysis was performed to analyze students’ incorrect responses. The result of this study shows that students did not acquire three characteristics of information literacy; i.e. recognizing information needs, locating and evaluating the quality of information, and making effective and ethical use of information. This result indicates students' low ability in information literacy.Keywords: information literacy, mathematical literacy, Programme for International Student Assessment (PISA)